Tindak Tutur â€œRequestâ€ Bahasa Inggris dalam Metode Role Play pada Mahasiswa Keperawatan - Priyastuti, Maria Theresia (CV. Global Health Science Group, 2020)
This research discusses the form of request and the strategy of request in English learning process using role play method. Objective: to describe the form of request and the strategy of request in English learning process using role play method. Method: descriptive qualitative with equal pragmatic methods using theory of Edmondson and House and Aijmer. The data were taken from role play conversation which contained speech act of request. The total sampling were used 20 groups when the nursing students did role play of giving health education. Data methods used listening and direct observation (participatory observation). Results: firstly, speech acts of assertive request in English learning that often used in role play conversations are